Convergências entre educação e neurociências: funções executivas na educação infantil - Zardo, Andressa Loise (2022)
Advances in neuroimaging technologies have allowed a greater clarification of brain functions which may mean a possible use of technologies in the field of education with a purpose of contributing to the teaching and learning processes. Educators are professionals who are in constant contact with students, so they are able to intervene in the learner´s neural processes, preparing them to receive school knowledge. Despite its potential, it is important to consider there are limitations regarding what neurosciences can provide to education, especially with regard to the social context, which is very expressive in learning. Considering these aspects, the present study compromises with educational neuroscience in the sense of integrating transdisciplinary knowledge that meets the objectives proposed by the school, which aims to improve the teaching and learning processes, relevant to practice and not favoring the biologization of education. In this way, the research was directed in order to answer the following question: how are executive functions articulated with pedagogical practices in early childhood education? Thus, this dissertation aimed to identify how the knowledge of neurosciences and education, focused on executive functions, can converge in order to contribute to pedagogical practice. Therefore, we divided this dissertation into three moments: the first consists of a literature review that brings the anatomical and historical aspects of neurosciences and their possible contributions to pedagogical practice. The second focuses on the contributions to pedagogical practice in executives in early childhood education, based mainly on studies and research by Adele Diamond. The third moment consists in a reflective analysis of the scientific production in neuroscience and education of what was shown to be relevant during the literature review. From this research, we can see that as neurosciences are present in diverse contributions to pedagogical practice, including, chronobiology of sleep, memory and attention processes, such as executive functions and music. In the research, several strategies were observed that can be used in the teacher's daily life and possibly for the development of executive functions. The work of training executive functions in the school environment can be crucial for better school performance later on. In the literature searches it was possible to notice that many neuroscientist authors approach learning, but few teachers teach education in approaching neurosciences. To some extent, talking about neuroscience in the field of education, in an transdisciplinary way, seems to be a challenge that, even in the face of its potential, has little credibility. Finally, it was also concluded that the figure of the teacher and his contribution, in this environment, is stigmatized since, despite one of the statements of a need to build a transdisciplinary field, taching knowledge has little space in educatinoal neurocience research, which only decreases the possibility of a dialogue between the medical, psychological and educational sciences.